2021
DOI: 10.1093/treephys/tpab013
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of non-structural carbon pools and their relationship to growth in two boreal conifer tree species

Abstract: In an attempt to comprehensively study the dynamics of non-structural carbon compounds (NCC), we measured the seasonal changes of soluble sugars, starch, lipids, and sugar alcohols in the leaves, branches, stem, and roots of the fast-growing Pinus contorta (pine) and slow-growing Picea glauca (spruce) trees growing in a boreal climate. In addition to measuring seasonal concentrations of these compounds, the relative contribution of these compounds to the total NCC pool within organs of trees (~8 m tall) was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…(2019), there was a significant reduction in branch NSC and a corresponding increment of stem NSC during April in both red oak and maple at the same site. A recent study has also suggested that storage in living bark tissue can be a source of NSC remobilisation for xylem formation (Schoonmaker et al ., 2021). This xylem NSC maintenance may cause C depletion in other organs and induce further feedbacks between source and sink activities (Hartmann & Trumbore, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…(2019), there was a significant reduction in branch NSC and a corresponding increment of stem NSC during April in both red oak and maple at the same site. A recent study has also suggested that storage in living bark tissue can be a source of NSC remobilisation for xylem formation (Schoonmaker et al ., 2021). This xylem NSC maintenance may cause C depletion in other organs and induce further feedbacks between source and sink activities (Hartmann & Trumbore, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, the allocation of NSCs may vary according to the species (Piper, 2011), the degree of water deficit (Martínez‐Vilalta et al, 2016; Santos et al, 2021), and the ability of the plant to store and transport these metabolites. Previous studies on the hydraulics or carbon metabolism of woody species in temperate (Palacio et al, 2007; Martínez‐Vilalta et al, 2014; Nardini et al, 2016; Tomasella et al, 2017; Palacio et al, 2018; Tomasella et al, 2019; Resco de Dios et al, 2020; Schoonmaker et al, 2021) and tropical (Bucci et al, 2003; Rivas et al, 2013; Rosell et al, 2020; Santos et al, 2021; Signori‐Müller et al, 2021) climates have shown that their responses are far from standard, being closely dependent on study conditions, selected species, and traits measured (Souza et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, affects photoassimilate transport (Chuste et al, 2020; McDowell et al, 2008; Sala et al, 2010). NSCs are the most important carbon reserves in deciduous and evergreen trees and can be used as a carbon source to satisfy the demands of metabolism, defense, and growth (Hoch et al, 2003; Schoonmaker et al, 2021). Moreover, NSCs play pivotal roles in plant tolerance to water deficit because of their ability to act as signaling molecules (Secchi & Zwieniecki, 2011), osmoprotectants, and reactive oxygen species scavengers (Regier et al, 2009; Rolland et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Resin tapping has been applied widely in mature slash pine plantations in China, and we aimed to investigate its influence on NSC allocation in plant tissues. In our study, we found that both tapped and control trees stored more NSC, starch and free sugars in winter than summer: it is likely that trees need more NSC to support growth and metabolism during the growing season and will store more NSC in winter as a resource for future use [ 41 ]. The concentrations of NSC, starch and free sugars in trunk phloem and root were reduced after resin tapping in summer, but the concentrations in root were lower in winter in tapped compared to control trees.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous resin tapping might be a trigger for trees to produce methyl jasmonate, which acts as a sensory signal and stimulates the plant to produce protective compounds. Such metabolism would use NSC from needle photosynthesis and might also stimulate the roots to absorb more mineral nutrients [ 41 , 42 ]. It was reported that white spruce ( Picea glauca ) trees increased the synthesis of jasmonic acid in roots and leaves to promote increased production of soluble carbohydrates for defense against spruce budworm [ 43 ].…”
Section: Discussionmentioning
confidence: 99%